Hubungan Lingkar Lengan Atas (LILA) dan Kenaikan Berat Badan Ibu Hamil Dengan Taksiran Berat Janin - Andi Ria Metasari; K Kamsiyati; E Ermawati (Jurnal Ilmiah Kesehatan, 2022)
Estimated fetal weight is an estimate of the weight of the fetus in the mother's womb so that knowing the estimated weight of the fetus in the womb will prevent the occurrence of low birth weight (LBW) babies. This study aims to determine the relationship between upper arm circumference (LILA) and weight gain of pregnant women with estimated fetal weight in the Watampone Community Health Center, Bone Regency. The design of this study was observational analytic with a cross sectional study design. The sample in this study was 100 pregnant women in the third trimester who came to check their pregnancy by using accidental sampling technique according to the inclusion criteria. The results of the study showed that there was a relationship between upper arm circumference (LILA) of pregnant women and the estimated weight of the fetus, p value = 0.000 and there was a relationship between weight gain of pregnant women and estimated fetal weight, p value = 0.000. For this reason, it is necessary to improve the antenatal care service system, especially in providing information to mothers about fulfilling nutritional intake needs during pregnancy so that mothers do not experience malnutrition that causes SEZ and will affect fetal growth and development resulting in low birth weight (LBW) babies.